Personal Identification Method of Robot with Whole-Body Sensing Mechanism - Arakawa, Junichi; Tsuji, Toshiaki; Tan, Desney ((2010) 36th Annual Conference on IEEE Industrial Electronics Society, 2010)
Haptic modality is one of the most important issues in man-machine communication. This paper introduces a personal identification technique based on force information of finger tracing that can be used for advanced man-machine communication systems. Compared to other biometric methods, the proposed method has an advantage of high security due to the invisible feature of force information. Experimental results show the validity of the proposed method.